2007
DOI: 10.3174/ajnr.a0506
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Headaches during Pregnancy: Correlation between Neurologic Examination and Neuroimaging

Abstract: BACKGROUND AND PURPOSE: Emergent evaluation of the pregnant headache patient requires rational selection of acute neuroimaging studies, yet guidelines do not exist. We investigated the demographic and clinical features that are predictive of intracranial pathologic lesions on neuroimaging studies in pregnant women with emergent headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 8 publications
3
15
0
1
Order By: Relevance
“…Headache is a well-known symptom in eclampsia/preeclampsia [8,9,10]. It is also common after delivery [11, 12]. It has further been suggested that there is a connection between preeclampsia and migraine [13].…”
Section: Discussionmentioning
confidence: 99%
“…Headache is a well-known symptom in eclampsia/preeclampsia [8,9,10]. It is also common after delivery [11, 12]. It has further been suggested that there is a connection between preeclampsia and migraine [13].…”
Section: Discussionmentioning
confidence: 99%
“…Ramchandren et al 16 reviewed 63 pregnant women presenting to an emergency department with headache, two-thirds of whom received neurologic consultation and all had neuroimaging, yielding 26.9% with secondary headache. An abnormal neurologic examination was more common in patients with secondary headache, but this did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines do not exist for diagnostic strategies in this patient population, developed algorithms are not validated, 14,15 and clinical series describing demographics, symptomatology, and diagnoses of pregnant women evaluated for acute headache are scarce. 16,17 We aimed to study a large number of pregnant women presenting with acute headache to the inpatient setting to better characterize demographics, comorbidities, symptoms, examination findings, rates, and risk factors of primary and secondary headache diagnoses.…”
mentioning
confidence: 99%
“…[22] Literatürde, hangi durumlarda hastalara kraniyel görüntüleme önerilmesi gerektiğine dair değişik çalışmalar mevcuttur. [23][24][25][26] Genel kabul gören endikasyonlar şunlardır: a) bireyin hayatındaki ilk ya da en kötü başağrısını yaşıyor olması, b) tipik aura dışında eşlik eden fokal nörolojik defisit, bilinç değişikliği, ense sertliği ya da papilödem varlığı, c) öksürük, efor ya da cinsel ilişki ile ortaya çıkan başağrısı, d) 50 yaş üzerinde, hamilelik ya da postpartum dönemde yeni gelişen başağrısı, e) ani başlangıçlı ya da giderek kötüleyen sürekli bir ağrı paterninin varlığı, f ) ateş, döküntü ya da temporal arter trasesinde hassasiyet gibi vasküliti düşündüren bulgular, g) kanser, AIDS ya da lyme hastalarında gelişen başağrısı.…”
Section: (A) (B)unclassified